Material flow improvement - Belime, Léo (My University, 2010)
Louis Vuitton’s workshops and their supply chains are continuously changing in order to meet growth in sales and ever-faster product-life cycles. Organizations evolve and new systems are implemented. In this context, the workshop needs to increase the control over its flow of material. This lack of control results in inappropriate supplies (generating material excess and/or shortages) or losses and wastes of material, which has financial consequences for the workshop. The analysis identified areas of potential improvement and broke down the project into three subjects: improving technical data reliability, defining the process of production ramp-downs and monitoring the performance of the warehouse. Each project started by a period of analysis, followed by proposals, implementation and follow-up. All of them appealed to “change management” practices. The projects brought concrete gains on material control. Bills of material and stock levels are more reliable, production ramp-downs are in control. The main outcomes of the projects are methods: production ramp-downs procedure, raw material quality monitoring, control process monitoring. The control of material flow is now set as a goal for the team, improvements are followed and shared. Thus this project contributed to give the workshop the means to sustain improvements on material flow. Keywords: Material flows, waste reduction, performance indicators
Keywords: Produktion; Produktionsteknik; Industriell organisation, administration och ekonomi; Production; Manufacturing engineering; Industrial organisation, administration and economics